The critique and transcendence of universal values through the humanity’s common values: a theoretical investigation on Marx’s thought on personal freedom - Yun Wang; Wenyu Liu; Peng Li (Trans/Form/Ação)
The concepts of “universal values” and “common values of all humanity” are often confused. Existing literature has examined the distinction between these two concepts within the philosophical domains of ontology, methodology, epistemology, historical perspectives and ethics. The innovation of this paper lies in its analysis from a more micro-level perspective, focusing on the concept of “individual freedom”. Marx’s notion of “personal freedom” is characterized as “concrete freedom,” referring to the “real individual” as historical, social and relational. In contrast, the liberal philosophers’ concept of “personal freedom” is seen as “abstract freedom,” where the individual is regarded as innate, natural and independent. Marx delved into the realm of material production, focusing on the individual’s labor and the relations of production. He advocated for the abolition of alienated labor, aiming for a society where, in a communist system, each person could achieve free and comprehensive development. The disparities in these notions of “personal freedom” reflect the fundamental distinctions between Marx’s “common values for all humanity” and Western “universal values”.